Analisis Tendangan Pisang Pesepak Bola - David Bandhaso; Rahmawati Munir; Adrianus Inu Natalisanto (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2022)
Banana kick is a type of soccer kick that uses the Magnus effect. The Magnus effect is a change in the direction of the ball's trajectory caused by the Magnus force. The force arises when a ball moving in air rotates on its axis. This research was conducted to analyze the ball entering the goal as a result of the Magnus force created by footballers. By means of Tracking Video Analysis and Modeling Tool software to several video tracks of football matches, it can be obtained the initial velocity, elevation angle, and angular velocity to determine the reach and heigh of the ball and the pertain Magnus force. The results of this study can be used in banana kick training.